Coexistence of Mature Cystic Teratoma and Endometrioma in an Ovarian Cyst - DAROUICHI.M; JC TILLE.; J DUBUISSON.; JOVANOVIC.S (Journal of Digestive Disorders And Diagnosis, 2017)
A rare association mature cystic teratoma (MCT) with endometrioma in the left ovary is reported in English literature. Coexistence MCT and endometrioma in the same ovary is extremely rare and its diagnostic is a challenge clinically and radiologically. To our knowledge we report the third case coexistence of a nonneoplastic endometrioma and benign neoplastic mature cystic teratoma in ovary.
Keywords: Mature teratoma cystic